Therapeutic Sources of Skeletal Muscle Regeneration from Volumetric Muscle Loss: A Narrative Review - Lee, Kwangjun; Park, Wonil; Hong, Kwang-Seok (Exercise science (Seoul, Korea), 2022)
PURPOSE: Minor skeletal muscle injuries can be repaired, but more extensive volumetric muscle loss (VML) leads to a permanent functional disability with ambiguous therapeutic outcomes, and reconstructive surgical procedures are constrained by donor tissue scarcity. This review assessed the considerable attention paid to biomaterials in healing damaged skeletal muscle.METHODS: A comprehensive search in PubMed, Web of Science, Google Scholar, and Wiley Online Library was conducted to obtain previous studies exploring the state of biocompatible tissue scaffolds for VML recovery.RESULTS: By regenerating the function of damaged skeletal muscle, tissue-engineered skeletal muscle construction could revolutionize the treatment of VML. However, transporting cells into the wounded muscle location presents a significant challenge because it may result in unfavorable immunological reactions. The development and validation of several biomaterials with varying physical and chemical natures to treat various muscle injuries have recently been undertaken to overcome this problem. This review discusses the relative benefits of satellite cells (SC), the most prevalent skeletal muscle stem cells employed to seed scaffolds.CONCLUSIONS: Biomaterials can be used with skeletal muscle stem cells and growth factors to repair VML because of their customizable and desirable physicochemical qualities. Owing to the capacity of SCs for self-renewal and their undifferentiated state, these cells are excellent candidates for cell therapy. A large gap exists between understanding SC behavior and how it can be used to repair and regenerate human skeletal muscle tissue. Thus, this review sought to portray the current knowledge on the lifespan of SCs and their involvement in exercise-induced muscle regeneration and hypertrophy.